Total free and free D-amino acid content of cheeses produced by different technologies: Preliminary report - Csapó, János; Csapóné Kiss, Zsuzsanna; Vargáné Visi, Éva; Albert, Csilla; Salamon, Rozália (Acta Agraria Kaposváriensis, 2005)
The concentration of total free AA and free D-AA were determined by ion exchange column chromatography and by high performance liquid chromatography in the outer layer and inner part of Ardrahan (Irish smear-ripened cheese) and Camembert cheeses, Danish blue, Emental, Gouda Mozzarella, Parmezan and five Cheddar cheeses produced by different technologies. It was established that the total free AA concentration was highest in Parmezan and Gouda cheeses (39000–24000 µmol/100 g), and lowest in Mozzarella and Cheddar cheese produced by different technologies (2400–7400 µmol/100 g), while the other cheeses examined contained 13000–19000 µmol/100 g free AA. The average concentrations of free D-AA in the different cheeses were the following: D-Asp 58 µmol/100 g (30.3%), D-Glu 117 µmol/100 g (15.8%), D-Ala 276 µmol/100 g (37.2%). The values in brackets are the free D-AA concentration as a percentage of total free (D + L) AA. The amount of free D-AA showed differences between cheeses. D-AA as a percentage of total free AA was changed 13.9–46.3% for D-Asp, 12.9–26.6% for D-Glu and 16.1–48.1% for D-Ala. Except for these three D-AA, the other D-AA were present in the cheeses at very low concentrations, at the limit of the identification and determination. In the case of Cheddar cheese concentrations of the D-AA were a little higher, when lactobacilli were added during cheese making.
Keywords: free amino acids; free D-amino acids; cheeses produced by different technologies